Moisture evolution in Central Asia since 26 ka: Insights from a Kyrgyz loess section, Western Tian Shan. (1st December 2020) - Li, Yue; Song, Yougui; Orozbaev, Rustam; Dong, Jibao; Li, Xinzhou; Zhou, Jie
Abstract: Central Asia (CA) is located in the hinterland of the Eurasian continent, and faces an extreme risk of continued aridification under the current global warming trend. To predict future climate change in CA, paleoclimate studies provide essential references. However, the mechanisms underlying climate changes in CA remain relatively poorly known. Here, we investigate moisture variations in CA, as recorded in a 6-m loess section in the Western Tian Shan, Kyrgyzstan, which has accumulated since ∼26 ka based on the radiometric AMS 14 C dating. We reconstructed the evolution of the wind regime and moisture conditions in the Western Tian Shan with a modified grain size index (GSIm ) and a new L∗ proxy (ΔL∗). While the frequency-dependent magnetic susceptibility (χfd ), redness (a∗) and yellowness (b∗) did not provide reliable paleoclimatic indicators, due to weak pedogenesis and other controlling factors. The GSIm records demonstrated a precipitation maximum in summer before ∼15 ka, shifting to a maximum in spring after ∼15 ka, probably associated with large-scale modulation of the latitudinal climatic zones and atmospheric circulation in response to retreat of the Northern Hemisphere ice sheets. Based on the ΔL∗ records, we place emphases on the important role of temperature-modulated evaporation in moisture evolution across CA; however, this has only influenced moisture evolution in spring and summer, with little effect on winter moisture conditions. Moreover, the ΔL∗ records may also indicate that atmospheric humidity can partly affect the long-term effective moisture variations. Highlights: Seasonal shift of precipitation at ∼15 cal ka triggered by the NHIS. Importance of evaporation driven by temperature in CA moisture evolution. Evaporation mainly worked on spring and summer moisture evolutions.